Calculation of Bearing Capacity and Deformation of Composite Pile Foundation with Long and Short Piles in Loess Areas - Tianzhong Ma; Yanpeng Zhu; Xiaohui Yang (Advances in Civil Engineering)
In order to calculate the bearing capacity and settlement deformation of composite pile foundations with long and short piles in collapsible loess areas, the theoretical approximate solution was used to obtain the location of the neutral point of single piles. Additionally, based on the equation to calculate the bearing capacity of multielement composite foundations, a method considering the negative frictional resistance was proposed for calculating the bearing capacity of composite pile foundations with long and short piles. Based on the shear displacement method and the principle of deformation control, an equation to calculate the displacement and deformation of a composite pile foundation was presented. A model test with different operating conditions, i.e., a single pile, four piles, and eight piles, was designed to verify the proposed calculation methods. The results show that the location of the neutral point has a significant influence on the single-pile negative frictional resistance, and the neutral point ratio of the calculation meets the value range of the practical project. When the load at the top of the pile is relatively small, the experimental curve is consistent with the theoretical calculation curve, whereas when the load is comparatively large, the theoretically calculated displacement increase at the top of the pile is greater than the measured one. Under the premise that the theoretical calculation is in good agreement with the results, the theoretical value is larger than the actual value. And it contributes to strengthening engineering safety.